Invasive versus conservative strategy in the very elderly with non‐ST‐elevation acute coronary syndrome: A meta‐analysis of randomized controlled trials. Issue 1 (19th November 2021) - Wang, Haiyan; Shi, Liye; Tian, Wen; Zhao, Shijie
Abstract : Aim: To investigate the optimal treatment strategy in patients older than 80 years with non‐ST‐segment elevation acute coronary syndrome (NSTE‐ACS). Methods: All published randomized, placebo‐controlled trials (RCTs) reporting on comparisons between invasive and conservative strategies for patients aged 80 years or older with NSTE‐ACS were identified. The literature search was performed using PubMed, EMBASE, Cochrane Library, and the ISI Web of Science, from their establishment to July 2021 with no language restriction. The pooled risk ratios (RRs) with 95% confidence intervals (CI) for dichotomous outcomes were calculated. Results: Three RCTs involving a total of 893 cases met the inclusion criteria. Compared with the conservative group, the invasive strategy could significantly improve the incidence rate of composite endpoint (I 2  = 21.9%; RR 0.727, 95% CI 0.619 to 0.855, P  < 0.001), recurrent myocardial infarction (MI) (I 2  = 0.0%; RR 0.585, 95% CI 0.441 to 0.776, P  < 0.001) and revascularization (I 2  = 0.0%; RR 0.239, 95% CI 0.126 to 0.455, P  < 0.001). However, no benefits were observed on outcomes of all‐cause death (I 2  = 0.0%; RR 0.888, 95% CI 0.681 to 1.160, P  = 0.384), cardiac death (I 2  = 0.0%; RR 0.769, 95% CI 0.412 to 1.433, P  = 0.408) and stroke (I 2  = 0.0%; RR 0.778, 95% CI 0.392 to 1.543, P  = 0.473). The major bleeding events were comparable between the two groups (I 2  = 0.0%; RR 1.582, 95% CI 0.622 to 4.025, P  = 0.336). Conclusions: Compared with a conservative strategy, the invasive treatment could reduce the incidence of composite endpoint, recurrent MI, and revascularization in the very elderly with NSTE‐ACS. However, no benefits were observed on mortality. Geriatr Gerontol Int 2022; 22: 36–41 .